Pelatihan Pemeliharaan Kesehatan Gigi dan Mulut dalam Mencegah Kepikunan pada Komunitas Pra-Lansia - Rizal, Muhammad Ihsan; Djamil, Melanie Sadono; Wulansari, Selviana; Hayunintyas, Ria Aryani; Tadjoedin, Fatimah Maria (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Dementia is described as a loss in cognitive abilities that leads daily tasks to become dysfunctional. Because this disease is a global health issue with no therapy, prevention and early detection are important priorities in its care. Periodontitis is one of the risk factors considered to be linked to dementia. Periodontitis is a complex chronic disease that causes destruction to the teeth's supporting tissues, specifically the alveolar bone, periodontal ligament, gingiva, and cementum. The buildup of dental biofilm because of poor oral hygiene is a risk factor for periodontal disease, which can proceed to periodontitis. Periodontitis is becoming more common as people become older, and it is one of the leading causes of tooth loss. By maintaining better oral hygiene, periodontal disease, a risk factor for dementia, can be reduced or prevented. It is anticipated that dental and oral maintenance education in the pre-elderly population will lower the risk of senility when people reach old age. Pre-elderly citizens (aged 45–59) in the Menteng Sukabumi region of Central Jakarta are the focus of promotion, education, and training in maintaining dental and oral hygiene. The pre-elderly residents will benefit from this training and counseling if they have a basic understanding of the connection between periodontal disease and senility and what can be done to avoid it. In conclusion, community service activities that focus on education and dental care are important steps to reduce the risk of dementia. Service activities must begin with raising awareness. Organizing free dental check-ups for the community, especially for those who cannot afford it, also needs to be encouraged.